2017
DOI: 10.1371/journal.pbio.1002591
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Genetic Incompatibilities between First-Step Mutations during Parallel Adaptation of Saccharomyces cerevisiae to a Common Environment

Abstract: Independently evolving populations may adapt to similar selection pressures via different genetic changes. The interactions between such changes, such as in a hybrid individual, can inform us about what course adaptation may follow and allow us to determine whether gene flow would be facilitated or hampered following secondary contact. We used Saccharomyces cerevisiae to measure the genetic interactions between first-step mutations that independently evolved in the same biosynthetic pathway following exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 56 publications
4
74
1
Order By: Relevance
“…In extreme cases, sign epistasis can cause a single substitution to have opposing functional or fitness consequences in different genetic backgrounds Harms and Thornton 2013;Shah et al 2015;Storz 2016;Ono et al 2017). Unlike our results, Natarajan et al (2015Natarajan et al ( , 2016 found that convergence in hemoglobin-oxygen affinity in high-altitude avian species did not evolve through a repeated order of mutations to hemoglobin.…”
Section: Resultscontrasting
confidence: 89%
“…In extreme cases, sign epistasis can cause a single substitution to have opposing functional or fitness consequences in different genetic backgrounds Harms and Thornton 2013;Shah et al 2015;Storz 2016;Ono et al 2017). Unlike our results, Natarajan et al (2015Natarajan et al ( , 2016 found that convergence in hemoglobin-oxygen affinity in high-altitude avian species did not evolve through a repeated order of mutations to hemoglobin.…”
Section: Resultscontrasting
confidence: 89%
“…This also supports the observation of moderate metalaxyl resistance in P. infestans F1 progeny from a cross between sensitive and highly resistant isolates . It has been reported that double mutations of yeast showed greater fitness than single or no mutation isolates in the presence of fungicide . Although the role of the corresponding mutations was not investigated in all organisms, different mutations of RPA190 in yeast did lead to different phenotypes such as N1203S and L1222S .…”
Section: Discussionsupporting
confidence: 73%
“…; and Ono et al. for discussion of environment‐specific hybrid incompatibilities). We consider our model to be one of “extrinsic” rather than “intrinsic” isolation because we do not consider traits such as gamete viability, which experience environment‐independent selection.…”
Section: Methodsmentioning
confidence: 99%